2014
DOI: 10.1680/macr.13.00230
|View full text |Cite
|
Sign up to set email alerts
|

New theoretical model for SSTT-confined HSC columns

Abstract: The concrete-confining method using low-cost steel straps, also known as the steel-strapping tensioning technique (SSTT), has proven to be effective in increasing the load-carrying capacity and ductility of high-strength concrete (HSC). However, the technique is restricted to short columns subjected to concentric loads as most of the studies on the SSTT have focused on concentrically loaded short HSC specimens. The performance of the SSTT in confining eccentrically loaded slender HSC columns is not fully under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…However, the increment in maximum load of HSC columns was found to decrease with the increase in confinement level, showing no proportional increment in maximum load with confinement level. A similar observation has been reported by Jiang and Teng , Ma et al and Johansson , indicating that there is a threshold strength improvement due to external confinement. 3.The post‐tensioning steel‐strap confinement enhanced the performance of the columns by postponing the crushing of concrete on the compressive side, which means it increased the column ductility. …”
Section: Discussionsupporting
confidence: 89%
“…However, the increment in maximum load of HSC columns was found to decrease with the increase in confinement level, showing no proportional increment in maximum load with confinement level. A similar observation has been reported by Jiang and Teng , Ma et al and Johansson , indicating that there is a threshold strength improvement due to external confinement. 3.The post‐tensioning steel‐strap confinement enhanced the performance of the columns by postponing the crushing of concrete on the compressive side, which means it increased the column ductility. …”
Section: Discussionsupporting
confidence: 89%
“…Due to the economic consideration, mostly the latter will be chosen as it requires less time, cheaper, easier and most importantly, it is highly effective. Past research works have proven that rapid repairing using confinement is effective in restoring the original strength of the concrete columns [7][8][9][10]. Besides, it was also reported that the confinement restored the ductility of damaged concrete as well [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the suitability of using steel straps as confining material has been experimentally investigated [1][2][3][4][5]. The steel straps used in these studies are recycled steel straps which are commonly used as packing strands for exporting good crates.…”
Section: Introductionmentioning
confidence: 99%